2013
DOI: 10.1111/php.12183
|View full text |Cite
|
Sign up to set email alerts
|

On the Formation of Thymine Photodimers in Thymine Single Strands and Calf Thymus DNA

Abstract: Solar light leads to thymine dimers that are mutagenic and primary cause of skin cancer. Here, we report absorption and synchrotron radiation circular dichroism (CD) spectra of Tn single strands with different number n of bases (n = 2-7, 10, 11) recorded after various 254 nm irradiation times. From a principal component analysis of the CD spectra, we extract fingerprint spectra of both the cyclobutane pyrimidine dimer (CPD) and the pyrimidine (6-4) pyrimidone photoadduct (64PP). Extending the CD measurements t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…As shown in Figure , the relative fluorescence change increased with an increase in the number of thymine–thymine pairs. The photochemical reaction did not preferentially occur at the end or middle of the strands as previously reported . Among the tested sequences, a random sequence as a control showed a relatively low level of fluorescence decrease as the UV irradiation time increased.…”
Section: Results and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As shown in Figure , the relative fluorescence change increased with an increase in the number of thymine–thymine pairs. The photochemical reaction did not preferentially occur at the end or middle of the strands as previously reported . Among the tested sequences, a random sequence as a control showed a relatively low level of fluorescence decrease as the UV irradiation time increased.…”
Section: Results and Discussionsupporting
confidence: 74%
“…The photochemical reaction did not preferentially occur at the end or middle of the strands as previously reported. 24 Among the tested sequences, a random sequence as a control showed a relatively low level of fluorescence decrease as the UV irradiation time increased. It has been shown that two nonsuccessively located thymines could form dimers as a result of interstrand-type reactions.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…At pH 4, on the other hand, more peaks are observed that may be related to a mix of photoproducts. Baggesen et al, using calf thymus DNA, demonstrated the possibility of formation of both photoproducts 51 (CDP and 64PP), being the possibility of 64PP formation higher at pH 4 than pH 7 due to the short distance between the thymine bases. A very close look at absorption data of TT sequence at pH 4 ( Figure S5) also reveals a small increase of absorbance at 325 nm, indicating the minor presence of 64PPs.…”
Section: Assessment Of Dna Integrity After Irradiationmentioning
confidence: 99%
“…VUVCD spectroscopy as well as conventional CD can also be applied to various systems such as DNA–protein interactions [152154] and DNA damage [155157]. Since these approaches provide important structural information that is closely related to the genetic and physiological functions of nucleic acids, VUVCD spectroscopy will certainly also be useful in genomic structural biology.…”
Section: Structural Analysis Of Nucleic Acidsmentioning
confidence: 99%